Martensitic Transition, Magnetic, Microstructural and Exchange Bias Properties of Melt Spun Ribbons of Mn-Ni-Sn Shape Memory Heusler Alloy - Sharma, Jyoti; Suresh, K. G.; Raja, M. Manivel; Walke, Pravin (Frontiers in Materials, 2020)
In present report, we have studied the structural, microstructural, magnetic, exchange bias (EB) properties and magnetoresistance (MR) in Mn rich (Mn at. ~50%) Mn50Ni50-xSnx (x=10) shape memory Heusler alloy ribbons, prepared by melt spinning method. These ribbons are found to exhibit a first order structural (i.e. martensitic) transition at around 205 K from the high temperature austenite to the low temperature martensite phase. The martensitic transition occurs at comparatively lower temperatures in these ribbons than that for the same bulk alloy. Curie temperature of the austenite phase (TCA) is found to be larger i.e. around room temperature than that for bulk alloy. A significant EB field (HEB) of around 960 Oe has been observed at 2 K for these ribbons, which is found to be comparable to that reported for other Heusler systems. The presence of EB effect in these ribbons is attributed to the coexistence of FM/AFM exchange interactions in the martensite phase. They are also found to show a maximum negative MR of around 12 % near the martensitic transition, for 50 kOe field change. Investigation of DC magnetization, AC susceptibility measurements and the observation of training effect (i.e. characteristic feature of EB) strongly corroborates with the coexistence of FM/AFM exchange interactions in the martensite phase of these ribbons, which results in the large EB. Effect of temperature and magnetic field on the EB properties and MR has also been studied here.